2021
DOI: 10.17509/jare.v3i1.32938
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Demand Potential and Need for Passenger Terminal Facilities at Cikembar Sukabumi Airport

Abstract: - West Java Province has a very unique and strategic geographic field challenge as a province with the largest population in Indonesia and as a province that is at the forefront of supporting the rapid dynamics of development in the capital city DKI Jakarta. In realizing equitable development, as stated in the West Java Provincial Medium-Term Development Plan (RPJMD) 2018-2023, infrastructure development is regulated in a priority scheme that aims to bring equitable development. One of the planned transportati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…During the emergence of a stigma in society that mosques are considered a safe place of refuge when a disaster occurs, on the other hand in some cases, mosques become dangerous places. For example, during the 2018 Lombok Earthquake, the NTB News reported that 115 mosques were badly damaged and could not be used (Setiawan et al, 2021) Figure 4, Jamiul Jamaah Mosque in Lombok, NTB, which was destroyed by the earthquake Source: antarfoto.com Meanwhile, in Central Sulawesi, the 7.4 SR earthquake, followed by a tsunami and liquefaction, in Sigi, Donggala, Parigi Moutong, and Palu City, resulted in 191 mosques being seriously damaged, some were missing, tilted, and collapsed so that they could no longer be used. The various phenomena of mosques and disasters above show the importance of mosque design in reducing the impact of disasters so that the mosque functions as a safe place to take refuge when a disaster occurs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the emergence of a stigma in society that mosques are considered a safe place of refuge when a disaster occurs, on the other hand in some cases, mosques become dangerous places. For example, during the 2018 Lombok Earthquake, the NTB News reported that 115 mosques were badly damaged and could not be used (Setiawan et al, 2021) Figure 4, Jamiul Jamaah Mosque in Lombok, NTB, which was destroyed by the earthquake Source: antarfoto.com Meanwhile, in Central Sulawesi, the 7.4 SR earthquake, followed by a tsunami and liquefaction, in Sigi, Donggala, Parigi Moutong, and Palu City, resulted in 191 mosques being seriously damaged, some were missing, tilted, and collapsed so that they could no longer be used. The various phenomena of mosques and disasters above show the importance of mosque design in reducing the impact of disasters so that the mosque functions as a safe place to take refuge when a disaster occurs.…”
Section: Resultsmentioning
confidence: 99%
“…"During the emergence of a stigma in society that mosques are considered a safe place of refuge when a disaster occurs, on the other hand in some cases, mosques become dangerous places. For example, during the 2018 Lombok Earthquake, the NTB News reported that 115 mosques were badly damaged and could not be used(Setiawan et al, 2021)…”
mentioning
confidence: 99%
“…In analyzing the frequency distribution of rainfall data, four methods are used, namely the normal distribution method, the normal log distribution method, the Gumbel distribution method, and the Pearson type III log distribution method (Setiawan et al, 2021).…”
Section: Frequency Distribution Analysismentioning
confidence: 99%
“…Based on the existing criteria in the field, the Leuwi Panjang terminal area does not yet meet the criteria as a TOD area, including poor human and vehicle circulation systems because they are not integrated between areas and the absence of signage makes visitors confused to carry out their activities, lack of proper arrangement good and clean in this area, as well as inadequate facilities to support the continuity of activities in it. These are the reasons for choosing the project location for the design of a mixed-use building based on TOD for the smooth continuity of the activities of the people of Bandung City in the Leuwi Panjang terminal area (Setiawan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%